GAMBARAN PENGETAHUAN MASYARAKAT TENTANG SWAMEDIKASI SAKIT GIGI DI RW 044 KELURAHAN BAHAGIA, BEKASI UTARA - Iskandar, Honey; Sukowati, Yudha; Meryta, Aries; Setyaningrum, Noor Affni (Jurnal Riset Kefarmasian Indonesia, 2022)
The practice of self-medication is a lot of medication errors. Medication errors due to a lack of drug information. Self-medication is defined as the selection and use of medicines both herbal and synthetic drugs by a person to treat a disease or symptom that is self-recognized. In self-medication, it is best to follow the rational drug use requirements. The use of a drug is said to be irrational if the possibility of negative impacts received by the patient is greater than the benefits. The purpose of this study was to find out the description of knowledge about dental pain self-medication in RW 044 Bahagia, North Bekasi in April 2020, regarding the understanding of dental pain self-medication, the use of chemical drugs in dental pain self-medication, the use of traditional medicines in self-medication dental pain, where to get medicine for self-medication of dental pain, the reasons for self-medication of dental pain, and a source of drug information in self-medication for dental pain. The research method used is a descriptive research method to the community at RW 044 with the provision that 1 KK completes 1 questionnaire, with an age range of 25-64 years. The results of this study have a sufficient level of knowledge of 70 respondents (53.03%), So it can be concluded that the picture of community knowledge in RW 044 Bahagia, North Bekasi is sufficient.